1951
DOI: 10.1002/j.2050-0416.1951.tb01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Pest Infestation Control in Breweries and Maltings

Abstract: Primary and secondary pests which have been found in barley stores and in maltings are listed, and the life histories of the more important pests (grain weevil, saw‐toothed grain beetle, khapra beetle, and rust‐red flour beetle) and the types of damage caused are described; an account is given of the modes of spread of infestation and of conditions which favour insect development. Preventive measures include regular inspection of grain and containers, hygiene and attention to details of bin structure and stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1955
1955
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Any damp areas will tend to accentuate this process of group formation. Freeman (1951Freeman ( , 1961 has suggested that Oryzaephilus can multiply rapidly and cause grain heating, while Howe (1956Howe ( , 1962 considers that it will only do so if the initial temperature is above 20°C. and the grain is either damp (of more than 16 per cent, moisture content) or dusty.…”
Section: Discussionmentioning
confidence: 99%
“…Any damp areas will tend to accentuate this process of group formation. Freeman (1951Freeman ( , 1961 has suggested that Oryzaephilus can multiply rapidly and cause grain heating, while Howe (1956Howe ( , 1962 considers that it will only do so if the initial temperature is above 20°C. and the grain is either damp (of more than 16 per cent, moisture content) or dusty.…”
Section: Discussionmentioning
confidence: 99%
“…Several published reviews, books, and manuals are available either on spraying equipment and application machinery or on insecticide chemical formulations and their active ingredients [ 27 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. However, a comprehensive overview of insecticide formulations based on their physical state during application is missing.…”
Section: Formulations Are Adapted According To Specific Routes Of Insect Body Entry Arthropod Diversity and Various Environmental Conditimentioning
confidence: 99%
“…Anoxic or hypoxic atmospheres are formed by gas molecules already present in atmospheric air. Freeman [ 32 ] defined fumigants as pesticide gases that can either pass through the cuticle of the insect or enter through the insect’s breathing system. Thoms and Busacca [ 45 ] defined fumigants as pesticides that are in a gaseous state upon contact with the target pest.…”
Section: Gas and Vapor Insecticide Application Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule the larvae attack the embryo point, but in cases of heavy infestation other parts of the grain may also be attacked. Freeman (1951) reports that the larvae are resistant to DDT and only slightly affected by gamma-BHC and are best controlled with pyrethrum sprays and dusts. The adults are susceptible to DDT and gamma-BHC so that measures designed to kill the adults before they oviposit should eradicate a population.…”
Section: August 1955jmentioning
confidence: 99%